FACTORS AFFECTING PUBLIC POLICY IMPLEMENTATION IN PALESTINE DURING COVID-19 PANDEMIC - Said Z S Abdalmenem; Rosillah Binti Jamil (Scholar Express Journals, 2021)
Public policy is seen as a fundamental requirement for development and competence in public-sector organisations. The effort to stop the spread of the COVID-19 epidemic, on the other hand, highlights the critical role that governments play in numerous policy areas, including public health. Furthermore, governance arenas aid in explaining the policy and governance choices made by different governments in their fight against the COVID-19 pandemic, public policy and the need to understand the reasons for observed differences in governance responses to the pandemic in different countries and jurisdictions, the paper demonstrates how examination of a, institutional, and strategic factors operating in policy and factors include elite panic and limited government attention span When elected officials encounter significant uncertainty, strategic variables include political concerns underpinning policy and governance decisions. Focusing on these characteristics and spaces aids state-centric governance theory in producing explanations rather than describing policy-making processes. Concepts for international development may be ambiguous and too ambitious at times, and they seldom take into consideration a country's unique circumstances, especially those of poor nations. According to the Worldwide Governance Report, the state of Palestine has low governance quality. The purpose of this study is to get a better understanding of the role of good governance in the Palestinian public sector. Another goal of this research is to look at the impact of transformational leadership styles in mediating the link between good governance and public policy execution. The research examined the findings acquired by combining the results of many investigations and presenting the final conclusions in a simpler way by evaluating various literatures and peer-reviewed papers. Found the conflicting interests in the formulation and implementation of public policy in dealing with COVID-19 Public policies are developed, debated, and other good governance norms are followed. Furthermore, such a long-term strategy may be critical to enhancing the impact of large public participation in reducing the spread of COVID-19. The results of this research are not only valuable in combating the present epidemic, but also have long-term implications for dealing with future pandemics.
Keywords: Transformational Leadership; Good Governance management; Public Policy Implementation; COVID-19 pandemics and Palestine